Exploring Characteristics of Digital Organizational Culture in Post COVID-19: A Systematic Literature Review - Muhammad Jasrif Teguh; Noermijati Noermijati; Wahdiyat Moko; Rofiaty Rofiaty (Journal of International Conference Proceedings (JICP), 2022)
This systematic literature research explored the characteristics of Digital Organizational Culture (DOC) in the Post Covid-19 period. Data on specific criteria of 63 DOC articles published between 2020 and 2022 were collected from the Google Scholar database using the Publish or Perish software. The data collected were analyzed using the matrix synthesis method and source suitability index technique. The results showed that ten DOC characteristics meet the criteria, including cross-functional collaboration, digital leadership, digital innovation culture, employee digital skills, digital technology change orientation, digital data management, risk-taking, customer digital experience focus, flexibility agility, and digital mindset. Consistency of key elements from at least three sources is required for further model development. The practical implications of this research are expected to serve as a guide for the implementation of DOC in the future, both in terms of its impact on the success of digital transformation and on organizational performance, especially in the post-COVID-19. Keywords: Digital Transformation, Digital Organizational Culture, Digital Corporate Culture, Post COVID-19